Root colonization and induction of pathogenesis-related genes by Pseudomonas aeruginosa strain UPMP3 in oil palm - Hamid, Sathyapriya (2012)
Basal stem rot (BSR) disease caused by Ganoderma boninense is the most destructive disease in oil palm plantations. The existing control measures for BSR disease such as mechanical, chemical and cultural practices have not been proven satisfactorily. Hence, BSR disease control is preferably achieved within the host plant through induction of resistance. Disease resistance induced by endophytes is effective under field conditions and offers a natural mechanism for biological control of plant disease. The efficient root colonization, proliferation in situ and persistence in planta have been emphasized on the selection of endophytes in disease control. To date, no study on colonization pattern of endophytic bacteria and endophytic bacteria-induced disease resistance has been reported in oil palm. Thus, the objectives of this study were (i) to tag the selected endophytic bacteria with -glucuronidase gene and green fluorescent protein to facilitate oil palm root colonization study by selected endophytic bacteria, (ii) to study the root colonization pattern of selected endophytic bacteria and (iii) to detect pathogenesis-related (PR) genes induced by selected endophytic bacteria in oil palm. Basic Local Alignment Search Tool (BLAST) analysis of recA gene sequence from Pseudomonas aeruginosa strain UPMP3 showed that P. aeruginosa strain UPMP3 shared 99% similarity with the clinical strain, P. aeruginosa PAO1. Similarly, Burkholderia cepacia strain UPMB3 had 99% similarity with B. cepacia strain LMG 14087 and B.cepacia strain ATCC17759, strains belonging to genovomar I, which is related to non-clinical sources. On the other hand, the absence of gusA gene in both, P.aeruginosa strain UPMP3 and B. cepacia strain UPMB3 demonstrated that tagging these strains with gusA was necessary in order to study their root colonization patterns in oil palm roots. For P. aeruginosa strain UPMP3, the bacterial cells treated with sterile double distilled water and 10% (v/v) glycerol following electroporation at the field strength 18 kV/cm resulted in transformation efficiency of ca 1 x 107 transformants/μg DNA. Meanwhile, gene transfer in B. cepacia strain UPMB3 was done via biparental mating and resulted in transconjugation efficiency of ca 1 x 104 transconjugants/donor CFU. However, tagged B. cepacia strain UPMB3 was not selected for further study due to plasmid instability. As the preliminary study of endophytic root colonization by tagged P. aeruginosa strain UPMP3 (stated as P. aeruginosa strain UPMP3::pHRGFPGUS) in 14 days showed promising results, the subsequent experiment was done with a more thorough study of colonization over 28 days. For epiphytic colonization, the rate increased from 5.76 log10 CFU g-1 FW to 8.19 log10 CFU g-1 FW while the endophytic colonization increased from 4.10 log10 CFU g-1 FW to 6.23 log10 CFU g-1 FW, over 28 days. Confocal laser scanning microscopic analysis of oil palm roots treated with treated P. aeruginosa strain UPMP3::pHRGFPGUS showed that this strain colonized the root elongation zones and lateral root emergence sites after inoculation. Following its ingress, P. aeruginosa strain UPMP3::pHRGFPGUS progressed from rhizodermis to exodermis and subsequently to cortical cells intercellularly. Then, the progression continued to the endodermis and finally the xylem vessels and pith. Besides, this strain was shown to associate itself with the cortical cells and vascular tissues of oil palm roots. Induction of pathogenesis-related genes, chitinase and -1, 3 glucanase by P. aeruginosa strain UPMP3 was studied in oil palm roots in the absence of pathogen. Chitinase and -1, 3 glucanase were induced with increasing period after inoculation and showed a peak value at 5 days after inoculation (DAI) and 7 DAI,respectively. The efficacy of P. aeruginosa strain UPMP3 in controlling BSR in oil palm seedlings was further screened in the glasshouse. When tested on oil palm seedlings inoculated with Ganoderma boninense PER71, P. aeruginosa strain UPMP3 suppressed G. boninense PER71 compared to the control with disease reduction of 78.36%. The excellent root colonization of P. aeruginosa strain UPMP3 coupled with the activation of defence mechanism in oil palm suggest that this strain could be used as the biocontrol agent against G. boninense. However, the use of P. aeruginosa strain UPMP3 as the biocontrol agent in agriculture has to be strictly monitored due to its potential in causing opportunistic infections in humans.